2018
DOI: 10.1620/tjem.244.1
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous BMP-7 Facilitates the Recovery of Cardiac Function after Acute Myocardial Infarction through Counteracting TGF-<i>β</i>1 Signaling Pathway

Abstract: Myocardial fibrosis after acute myocardial infarction (AMI) is one of the main causes of myocardial remodeling and heart function abnormalities. Bone morphogenetic protein-7 (BMP-7) has been reported to play essential roles in anti-fibrosis. In this study, we demonstrated the role of exogenous BMP-7 on myocardial fibrosis and heart function recovery after AMI. A rat model of AMI was established via ligation of the left anterior descending coronary artery (LAD). Twenty rats were grouped into sham group which un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…BMP-7 treatment significantly attenuated myocardial fibrosis, reduced the infarct size, and improved cardiac function. In addition, this study also reported that BMP-7 treatment inhibited myocardial fibrosis by attenuating TGF-β signaling and its downstream effectors Smad-2 and Smad-3 [211]. Furthermore, the beneficial role of BMP-7/Smad signaling has been shown in fibrotic disease of the heart [212,213].…”
Section: Bmp-7 Inhibits Inflammation and Adverse Remodeling In The Inmentioning
confidence: 53%
See 3 more Smart Citations
“…BMP-7 treatment significantly attenuated myocardial fibrosis, reduced the infarct size, and improved cardiac function. In addition, this study also reported that BMP-7 treatment inhibited myocardial fibrosis by attenuating TGF-β signaling and its downstream effectors Smad-2 and Smad-3 [211]. Furthermore, the beneficial role of BMP-7/Smad signaling has been shown in fibrotic disease of the heart [212,213].…”
Section: Bmp-7 Inhibits Inflammation and Adverse Remodeling In The Inmentioning
confidence: 53%
“…Moreover, exogenous administration of BMP-7 downregulates myocardial interstitial fibrosis as well as kidney fibrosis by inhibiting TGF-β signaling pathway and protects cardiac function. Recently, Jin et al demonstrated that exogenous BMP-7 facilitates cardiac function recovery after acute myocardial infarction by attenuating myocardial fibrosis through counteracting TGF-β1 signaling pathway [211]. In this study, the group established acute myocardial infarction by ligating the left anterior descending artery with and without BMP-7 treatment.…”
Section: Bmp-7 Inhibits Inflammation and Adverse Remodeling In The Inmentioning
confidence: 87%
See 2 more Smart Citations
“…Exogenouos administration of BMP7 improves left ventricular remodeling and function in acute myocardial infarction. 47 Trappin 2 is a serine protease inhibitor, and it has anti-inflammatory actions on the mucosal surfaces. 48 It also has anti-retrovirus activities on the mucosal surfaces.…”
Section: Streptococcus Pyogenes' Lysate Effects and Heat Map Analysismentioning
confidence: 99%